A vueltas con el desarrollo comunitario: características, reflexiones y retos - Rubio, José Antonio (Cuadernos de Trabajo Social, 2006)
The following article presents a work model of social organization based on participatory democracy, both for the organized population as well as for the population not yet organized, with the goal of improving not only their material living conditions but also their capacity to choose: their autonomy. It presents a definitive process of integrated development in which the golden rule is that everyone, collectively or individually, who wishes may participate in the process. The structure of some Community Plans, put into action in different areas of Spain, is used to illustrate what has been described here.